The influence of joint rigidity on impact efficiency and ball velocity in football kicking - Peacock, J. C. A.; Ball, K. (Journal of Biomechanics, 2018)
Executing any skill with efficiency is important for performance. In football kicking, conflicting and non-significant results have existed between reducing ankle plantarflexion during foot-ball contact with impact efficiency, making it unclear as to its importance as a coaching instruction. The aims of this study were to first validate a mechanical kicking machine with a non-rigid ankle, and secondly compare a rigid to a non-rigid ankle during the impact phase of football kicking. Measures of foot-ball contact for ten trials per ankle configuration were calculated from data recorded at 4000?Hz and compared. The non-rigid ankle was characterised by initial dorsiflexion followed by plantarflexion for the remainder of impact, and based on similarities to punt and instep kicking, was considered valid. Impact efficiency (foot-to-ball speed ratio) was greater for the rigid ankle (rigid = 1.16 ± 0.02; non-rigid = 1.10 ± 0.01; p < 0.001). The rigid ankle was characterised by significantly greater effective mass and significantly less energy losses. Increasing rigidity allowed a greater portion of mass from the shank to be used during the collision. As the ankle remained in plantarflexion at impact end, stored elastic energy was not converted to ball velocity and was considered lost. Increasing rigidity is beneficial for increasing impact efficiency, and therefore ball velocity.